Cultural Heritage and Historical Narratives in The Era of Globalization - Nabijonov Furqatjon Valijon ogli (Indonesian Journal Publisher, 2026)
This article examines the transformation of cultural heritage and historical narratives in the context of globalization. Particular attention is paid to the ways in which global cultural, informational, and economic processes influence the interpretation, preservation, and representation of historical memory and cultural identity. The study analyzes the tension between globalizing tendencies that promote cultural standardization and local efforts aimed at safeguarding national heritage and unique historical narratives. It is argued that globalization not only poses challenges to traditional forms of cultural transmission but also creates new opportunities for reinterpreting and revitalizing cultural heritage through transnational communication, digital technologies, and intercultural dialogue. The article emphasizes the role of historical narratives as a key mechanism for maintaining social cohesion, cultural continuity, and collective identity in an increasingly interconnected world. Based on a socio-philosophical and cultural analysis, the study highlights the necessity of developing balanced strategies that integrate global openness with the protection of cultural diversity and historical authenticity